MENAKAR MODEL PEMBELIAN LANGSUNG RUMAH NEGARA DI INDONESIA - Ariyana Qodri, Resi (Politeknik Keuangan Negara STAN, 2019)
The study explicates the formulation of basic criteria in decision making process of house selection based on international best practice and established regulation. The normative jurisprudence approach and systematic review methodology were implemented to fulfill research objective. The critical sources of information relied on 346 journal articles and 5 informants. Researcher exercised thematic analysis to extract the data collected. The findings proposed an interesting discourse: the fastest way to execute cooperative house selection is by buying a house directly from the developer.